Cytological Characteristics of Mucose Cell and Vaginal Temperature and pH During Estrous Cycle in Local Sheep - Rasad, Siti Darodjah; Setiawan, Rangga (ANIMAL PRODUCTION, 2017)
Aim of this study was to examine the characteristics cytology of mucous cell-,temperature- and pH vagina during estrous cycle in local sheep.  31local sheep were synchronized with vaginal sponge consist of 20  mg  progesterone hormone before carried out observations of cytology of cells from the vaginal mucose through vaginal swabs, temperature and pH of the vagina.  Vaginal swabs were collected daily at 7 am for a weeks.Vaginal temperature and pH measurement is carried out twice a day, at 07.00 am and 15.00 pm for a weeks after vaginal swabs. Smears of the swab were then prepared on glass slide and they were stained with Giemsa.  Vaginal epithelial cells; Parabasal, intermediate and superficial cells were counted and their percentages during pro-estrous, estrous and di-estrous were determined. Di-estrous was characterized by the absent of superficial cells in the epithelial vagina. Pro-estrous was characterized by the increasing progressively of intermediate/superficial cells in epithelial vagina, whereas estrous was characterized by the presence of superficial/cornification cells in most epithelial vagina. Based on the dominance of superficial cell, the number of sheep identified as estrous is highest on third day, with 52%.  Observation on vaginal temperature also resulting that the highest temperature values obtained on the third day of 39,08±0.28°C.  It could be effected of the vaginal pH during the observation. Underthe influence ofestrogen, the epithelial vaginalcellssynthesizeand accumulateglycogenin large quantitiesdepositedin the lumen ofvagina. Vaginal bacteriametabolizethe glycogenformlactic acid, which causesvaginal pHis low.The pH conditions prevent from pathogenic microorganisms and fungi. Increased estrogenal so cause cell proliferation through the thickening of the epithelium lining of the vagina so that the cells differentiate.Increasing of glycogenin the superficial cells, and  ceratin cells found in the cytoplasm of cells, as well as acidic pH in the lumen vagina causing changes in the chemical composition of each cell (Zaid, 2011).It can be concluded that during estrous phase, cytology of  vaginal mucose cell is dominated by superficial cell and vaginal temperature is increasing as well as pH of vagina.